Smart materials and Green Synthesis: The perfect match for the future - Pizzorno Backx, Bianca (International Research Journal of Multidisciplinary Technovation, 2021)
Materials science seeks the development of new materials with optimized characteristics. The union of various areas as chemistry, physics, nanotechnology, biology, and medicine catalyzes news materials. Smart materials react to external stimuli by modifying their chemical, mechanical, magnetic, optical, electrical, thermal properties. They have superior efficiency to the materials currently available and promise many advantages to their consumers. However, smart materials must be associated with sustainable technological progress. As a result of highly evolved technologies and intense laboratory research, their final characteristics must be connected with sustainable protocols. In addition to a significant difference associated with a wide application in various areas as textile industry, construction, medicine, drugs delivery, microorganisms’ detection, smart materials must not pollute from production to disposal, and more than that, they must seek compensation for the harmful effects of this evolution on nature. In this way, smart materials will be an excellent advantage for the future and the environment.